2019
DOI: 10.2174/1574887114666190809160419
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine versus Midazolam-Fentanyl in Procedural Analgesia Sedation for Reduction of Anterior Shoulder Dislocation: A Randomized Clinical Trial

Abstract: Background: Shoulder joint dislocation is the most common dislocation of joints in the body. To reduce the anterior shoulder dislocation, it is necessary to have analgesia and sedation. Methods: In this randomized clinical trial, patients were divided into two equal groups. Group I received midazolam-fentanyl (0.05 mg/kg fentanyl at a dose of 1 µg/kg) for 10 minutes and group II received dexmedetomidine (1 µg/kg in the initial dose and then 0.2 µg/kg/h) for 10 minutes. The levels of analgesia according to VA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Study designs included 11 RCTs, 22,32–41 13 cohort studies and other nonrandomized studies, 19–21,23,42–50 and 11 case series and case reports 12,51–60 . Six of the included studies were conference abstracts 20,21,40,47,50,56 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Study designs included 11 RCTs, 22,32–41 13 cohort studies and other nonrandomized studies, 19–21,23,42–50 and 11 case series and case reports 12,51–60 . Six of the included studies were conference abstracts 20,21,40,47,50,56 .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Chumpitazi et al 47 did find that intranasal administration of DEX for procedural in pediatric patients was not associated with increased ED length of stay compared to IV ketamine (likely due to delays involved in establishing IV access in children). However, it is not clear from the included studies that the onset of appropriate sedation after administration of IV DEX, which could take up to 8–10 min in adults, 32,39 would be consistent with usual ED procedural sedation practices.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Although the data are limited, a few studies have shown that DEX may reduce the need for endotracheal intubation in patients with alcohol withdrawal, and be a safe and effective procedural sedation agent. [6][7][8][9] Given the lack of data and trials regarding DEX use in the ED, there is a significant knowledge gap and lack of familiarity regarding the use of this agent. Furthermore, as DEX has consistently been shown to increase the incidence of hypotension and bradycardia, its safety profile in the ED during routine use is unknown as well.…”
Section: How Does This Improve Population Health?mentioning
confidence: 99%